Heritable symbiont producing nonribosomal peptide confers extreme heat sensitivity and antifungal protection on its host - Gerald P. Maeda; Vy Dang; Mary Katherine Kelly; Aadhunik Sundar; Ryan L. W. Arnott; Edward M. Marcotte; Nancy A. Moran (Proceedings of the National Academy of Sciences, 2025)
Insects frequently form associations with maternally transmitted symbiotic bacteria. This transmission mode ensures that symbiont-conferred effects, both beneficial and negative, are passed onto offspring. Here, we report an extreme example of symbiont-mediated temperature sensitivity imposed by a vertically transmitted, defensive symbiont. Pea aphids infected with the bacterial endosymbiont, Fukatsuia symbiotica, resist infection by fungal pathogens but produce few or no offspring when moved from cool (15 °C) to mildly warmer temperatures (20 °C). This temperature-dependent reduction in host fitness is associated with increased symbiont abundance, disordered symbiont localization, and high expression of a horizontally acquired nonribosomal peptide synthetase (NRPS) locus. This NRPS operon is syntenic with the locus responsible for the production of Herbicolin A, a known antifungal produced by some plant-associated Erwiniaceae . Activity of chemical extracts from infected aphids is predictive of in vivo protection against entomopathogenic fungi, indicating that an Herbicolin A–like molecule is the likely source of Fukatsuia’s protective effects against fungal pathogens. Injection of the same chemical extracts into naive aphids partially recapitulates developmental defects observed in natural infections at 20 °C, suggesting that increased levels of this compound contribute to disrupted embryonic development. Finally, the purification of the causal agent revealed Fukatsuia produces a compound similar but not identical to Herbicolin A, that exhibits both antifungal and hemolytic activity. These results suggest that F. symbiotica infection imposes a trade-off between antifungal defense and disrupted embryonic development, mediated by a single genetic locus.